Physical-chemical properties and cytotoxicity analysis of 5 different endodontic sealers - Almeida, Marcela Milanezi de (2017)
The aim of this study was to analyze the radiopacity, setting time, flowability, pH, calcium ion release, solubility and cytotoxicity of bioceramic cements Totalfill BC Sealer and Totalfill BC RRM, and compare them with AH Plus, MTA Fillapex and MTA Angelus. The groups were divided and compared among them according to the filling and retro-filling cement functions. Totalfill BC Sealer was compared with AH Plus and MTA Fillapex; and Totalfill BC RRM retrofilling cement with MTA Angelus. For radiopacity analysis, specimens were placed in metal rings measuring 10x1 mm placed on occlusal film together with the aluminum scale. Digora 1.51 software was used to evaluate the digitized images and determine radiographic density. Setting time was tested in accordance with the American Society for Testing and Materials C266-08 standard specifications, but specimens were fabricated in accordance with the International Organization for Standardization 6876: 2001. Flow was tested in accordance with ANSI/ADA No.57/200 specifications. In total 30 acrylic teeth were filled with filling-cements and 20, with (retrograde cavity) retro-filling cements. All teeth were immersed in ultrapure water for pH and calcium ion release measurement (atomic absorption spectrophotometer) for time intervals of 1, 3, 24, 72, 168 and 360 hours. Solubility was tested by scanning and digitizing 50 acrylic teeth twice by Micro- CT, before and after immersion in ultrapure water for time intervals of 168, 360 and 720 hours. The images were reconstructed and volume (mm3) values of samples obtained by means of CTan software (CTan v1.11.10.0, SkyScan). The in vitro effects on cells were analyzed at concentrations of 100, 50, 10, 5, 1 mg/mL, and 0 mg / mLnegative control group and recorded in time intervals of 24, 48 and 72 hours by MTT reduction assay. The results were statistically analyzed by the ANOVA, Tukey, Kruskal-Wallis and Dunn tests (P<0.05). All radiopacity values according to ISO 6876/2001, AH Plus (7.86 mm Al) being the most radiopaque followed by Totalfill BC Sealer (4.84 mm Al), MTA Fillapex (3.41 mm Al), Totalfill BC RRM (6.8 mm Al), and MTA Angelus (6.7 mm Al). The following values were the initial and final setting time (in hours), respectively: AH Plus (8 and 15); Totalfill BC Sealer (11 and 24); MTA Fillapex (13 and 26); MTA Angelus (10 and 120 minutes) and Totalfill BC RRM (3 hours and 22 hours). In flow analysis, the cements behaved as follows: MTA Fillapex (47 mm), Totalfill BC Sealer (41.5 mm), Totalfill BC RRM (33.5 mm), AH Plus (33 mm) e MTA Angelus (17.5 mm) (p < 0.05). pH analysis showed in general the lowest values for AH Plus cement, followed by Totalfill BC RRM, MTA Angelus, MTA Fillapex and Totalfill BC Sealer. AH Plus showed the highest Ca2+ release in time interval 1 hour (1.38 mg/L); MTA Fillapex, in 360 hours (3.81 mg/L); MTA Angelus, 1 hour (1.38 mg/L); Totalfill BC Sealer, 360 hours (6.77 mg/L) and Totalfill BC RRM, 360 hours (3.81 mg/L). Almost all the sealers presented solubility lower than 3% in all periods, as recommended by ISO 6876/2001. Whereas, the MTA Fillapex solubility value was higher than 5% in all periods. Relative to cytotoxicity, all the cements were shown to be toxic at the concentration of 100 mg/mL, however, Totalfill BC Sealer and Totalfill BC RRM showed the best cell viability result compared with the other cements tested. We concluded that all root canal filling and root retro-filling complied with the requisites of radiopacity, setting time, flow, pH, calcium ion release, solubility and cytotoxicity. With the exception of the MTA Fillapex that not only fulfilled the requirement of solubility. Of the sealers, Totalfill BC Sealer was outstanding: it showed the highest pH and Ca2+ release, and lowest cytotoxicity. Among the retrofilling cements, Totalfill BC RRM maintained its high pH, higher Ca2+ release, and lower cytotoxicity.